Stability enhancement of Celastrus paniculatus seed oil by loading in niosomes - Warintorn Ruksiriwanich (2018)
Objective: To investigate the bioactive compounds, biological activities and also develop the stability enhancement system for bioactive compounds in Celastrus paniculatus seed oil (CPSO) Method: This study has investigated the bioactive compounds including fatty acid profile and total phenolic content, antioxidative and tyrosinase inhibition activities of CPSO. Then, various blank niosomes formulations were prepared. The stability of CPSO was enhanced by loading CPSO in niosomes, CPSO loaded niosomes were determined their physical properties such as size, zeta potential and chemical stability of oleic acid. Results: CPSO gave not only high content of fatty acids especially cis-9- oleic acid (43.99 % w/w) but also the total phenolic compounds, γ-tocopherol and α-tocopherol that played an important role for the tyrosinase inhibition activity. CPSO exhibited superior tyrosinase inhibition activity than the standard ascorbic acid, kojic acid and arbutin. The maximum loading of the CPSO in selected niosomes (1:1 molar ratio of Tween61:cholesterol) was 2.00 % w/v with the average particle size of loaded niosomes about 230 nm and zeta potential of -46 mV. In the stability study, the CPSO loaded niosomes showed higher oleic acid content than CPSO solution indicating the substance protection after loading in niosomes after 3 months storage. Conclusion: Niosomes loaded with CPSO appeared to be a suitable method for the stability enhancement of the CPSO bioactive compounds because of not only the low toxicity, biodegradable, biocompatible, non-immunogenic but also skin penetration enhancer of niosomes as well.